Prevalence of Pulmonary Tuberculous Lesions in Cattle Slaughtered in Abattoirs in Northeastern Nigeria - I. O. Igbokwe; I. Y. Madaki; S. Danburam; J. A. Ameh; M. M. Aliyu; C. O. Nwosu (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2001)
A survey of tuberculosis in cattle was carried out in four abattoirs located in Maiduguri, Damboa, Damaturu and Gashua in Northeastern Nigeria from 1994 to 1998. Out of 1,698,000 slaughtered head of cattle examined at postmortem, 2.8% (95% confidence interval: 2.76–2.84) had pulmonary tuberculous lesions. The prevalences varied from 1.9% in Damaturu abattoir to 20.0% in Damboa abattoir. The annual prevalences during the study period varied from 2.3 to 4.7%. The monthly prevalences showed sporadic high prevalences above the endemic level. It is concluded that bovine TB is still endemic in the region with indications of epidemic proportions existing in Damboa area. Therefore, it is necessary for the Federal Government to consider and implement control measures to limit the spread of the disease among cattle and to human populations.